Asymmetric organocatalyzed synthesis of coumarin derivatives - Moreira, Natália Menezes; Martelli, Lorena Suelen Ribeiro; Corrêa, Arlene Gonçalves (Beilstein Journal of Organic Chemistry, 2021)
Coumarin derivatives are essential scaffolds in medicinal and synthetic chemistry. Compounds of this class have shown important activities, such as anticancer and antiparasitic, besides the commercially available drugs. These properties led to the development of efficient and greener synthetic methods to achieve the 2H-chromen-2-one core. In this context, the advances in asymmetric organocatalyzed synthesis of coumarin derivatives are discussed in this review, according to the mode of activation of the catalyst.
Keywords: asymmetric synthesis; green chemistry; 2H-chromen-2-one; organocatalysis

(untitled) - Wu, Y.; Xu, J.; Liu, Y.; Zeng, Y.; Wu, G. (Front. Oncol., 2020)

(untitled) - Qin, H.-L.; Zhang, Z.-W.; Ravindar, L.; Rakesh, K. P. (Eur. J. Med. Chem., 2020)

(untitled) - Prusty, J. S.; Kumar, A. (Mol. Diversity, 2020)

(untitled) - Gonçalves, G. A.; Spillere, A. R.; das Neves, G. M.; Kagami, L. P.; von Poser, G. L.; Canto, R. F. S.; Eifler-Lima, V. (Eur. J. Med. Chem., 2020)

(untitled) - Pires, C. T. A.; Scodro, R. B. L.; Cortez, D. A. G.; Brenzan, M. A.; Siqueira, V. L. D.; Caleffi-Ferracioli, K. R.; Vieira, L. C. C.; Monteiro, J. L.; Corrêa, A. G.; Cardoso, R. F. (Future Med. Chem., 2020)

(untitled) - Brenzan, M. A.; Santos, A. O.; Nakamura, C. V.; Filho, B. P. D.; Ueda-Nakamura, T.; Young, M. C. M.; Côrrea, A. G.; Júnior, J. A.; Morgado-Díaz, J. A.; Cortez, D. A. G. (Phytomedicine, 2012)

(untitled) - Alvim, J., Jr; Dias, R. L. A.; Castilho, M. S.; Oliva, G.; Corrêa, A. G. (J. Braz. Chem. Soc., 2005)

(untitled) - Kontogiorgis, C.; Detsi, A.; Hadjipavlou-Litina, D. (Expert Opin. Ther. Pat., 2012)

(untitled) - Delogu, G. L.; Matos, M. J. (Curr. Top. Med. Chem., 2017)

(untitled) - Kang, S. Y.; Lee, K. Y.; Sung, S. H.; Park, M. J.; Kim, Y. C. (J. Nat. Prod., 2001)

(untitled) - Vanzolini, K. L.; Vieira, L. C. C.; Corrêa, A. G.; Cardoso, C. L.; Cass, Q. B. (J. Med. Chem., 2013)

(untitled) - da Silva, J. I.; de Moraes, M. C.; Vieira, L. C. C.; Corrêa, A. G.; Cass, Q. B.; Cardoso, C. L. (J. Pharm. Biomed. Anal., 2013)

(untitled) - Lourenço Vanzolini, K.; Jiang, Z.; Zhang, X.; Curcino Vieira, L. C.; Gonçalvez Corrêa, A.; Lucia Cardoso, C.; Bezerra Cass, Q.; Moaddel, R. (Talanta, 2013)

(untitled) - Kumar, N.; Udayabhanu; Alghamdi, A. A.; Mahadevan, K. M.; Nagaraju, G. (J. Mol. Struct., 2021)

(untitled) - Sun, X.-y.; Liu, T.; Sun, J.; Wang, X.-j. (RSC Adv., 2020)

(untitled) - Fedorov, A. Y.; Nyuchev, A. V.; Beletskaya, I. P. (Chem. Heterocycl. Compd., 2012)

(untitled) - Lončarić, M.; Gašo-Sokač, D.; Jokić, S.; Molnar, M. (Biomolecules, 2020)

(untitled) - Gaudino, E. C.; Tagliapietra, S.; Martina, K.; Palmisano, G.; Cravotto, G. (RSC Adv., 2016)

(untitled) - Varma, R. S. (ACS Sustainable Chem. Eng., 2016)

(untitled) - Molnar, M.; Lončarić, M.; Kovač, M. (Curr. Org. Chem., 2020)

(untitled) - Chandrakar, K.; Patel, J. L.; Mahapatra, S. P.; Penta, S. (Curr. Org. Chem., 2020)

(untitled) - Anastas, P. T.; Kirchhoff, M. M.; Williamson, T. C. (Appl. Catal., A, 2001)

(untitled) - Priyanka; Sharma, R. K.; Katiyar, D. (Synthesis, 2016)

(untitled) - Kanchana, U. S.; Diana, E. J.; Mathew, T. V.; Anilkumar, G. (Appl. Organomet. Chem., 2020)

(untitled) - Alshibl, H. M.; Al-Abdullah, E. S.; Alkahtani, H. M. (Curr. Bioact. Compd., 2020)

(untitled) - Calcaterra, A.; D’Acquarica, I. (J. Pharm. Biomed. Anal., 2018)

(untitled) - Moyano, A.; Rios, R. (Chem. Rev., 2011)

(untitled) - Holland, M. C.; Gilmour, R. (Angew. Chem., Int. Ed., 2015)

(untitled) - Nielsen, M.; Worgull, D.; Zweifel, T.; Gschwend, B.; Bertelsen, S.; Jørgensen, K. A. (Chem. Commun., 2011)

(untitled) - Halland, N.; Hansen, T.; Jørgensen, K. A. (Angew. Chem., Int. Ed., 2003)

(untitled) - Echemendía, R.; de La Torre, A. F.; Monteiro, J. L.; Pila, M.; Corrêa, A. G.; Westermann, B.; Rivera, D. G.; Paixão, M. W. (Angew. Chem., Int. Ed., 2015)

(untitled) - Rueping, M.; Merino, E.; Sugiono, E. (Adv. Synth. Catal., 2008)

(untitled) - Bojanowski, J.; Skrzyńska, A.; Albrecht, A. (Asian J. Org. Chem., 2019)

(untitled) - Enders, D.; Niemeier, O.; Straver, L. (Synlett, 2006)

(untitled) - Enders, D.; Fronert, J.; Bisschops, T.; Boeck, F. (Beilstein J. Org. Chem., 2012)

(untitled) - Reddy, U. V. S.; Chennapuram, M.; Seki, C.; Kwon, E.; Okuyama, Y.; Nakano, H. (Eur. J. Org. Chem., 2016)

(untitled) - Lim, Y.-J.; Kim, D.-Y. (Bull. Korean Chem. Soc., 2012)

(untitled) - Lee, Y.-T.; Das, U.; Chen, Y.-R.; Lee, C.-J.; Chen, C.-H.; Yang, M.-C.; Lin, W. (Adv. Synth. Catal., 2013)

(untitled) - Ren, C.; Wei, F.; Xuan, Q.; Wang, D.; Liu, L. (Adv. Synth. Catal., 2016)

(untitled) - Hack, D.; Chauhan, P.; Deckers, K.; Hermann, G. N.; Mertens, L.; Raabe, G.; Enders, D. (Org. Lett., 2014)

(untitled) - Sonsona, I. G.; Marqués-López, E.; Gimeno, M. C.; Herrera, R. P. (New J. Chem., 2019)

(untitled) - Kumagai, J.; Kohari, Y.; Seki, C.; Uwai, K.; Okuyama, Y.; Kwon, E.; Nakano, H. (Heterocycles, 2015)

(untitled) - Zhu, L.; Zhang, L.; Luo, S. (Org. Lett., 2018)

(untitled) - Zhu, X.; Lin, A.; Shi, Y.; Guo, J.; Zhu, C.; Cheng, Y. (Org. Lett., 2011)

(untitled) - Kowalczyk, D.; Albrecht, Ł. (Adv. Synth. Catal., 2018)

(untitled) - Sun, J.-C.; Wang, X.-H.; Ji, C.-B.; Peng, Y.-Y.; Zeng, X.-P. (J. Org. Chem., 2020)

(untitled) - Bugaut, X.; Glorius, F. (Chem. Soc. Rev., 2012)

(untitled) - Yetra, S. R.; Roy, T.; Bhunia, A.; Porwal, D.; Biju, A. T. (J. Org. Chem., 2014)

(untitled) - Lv, H.; You, L.; Ye, S. (Adv. Synth. Catal., 2009)

(untitled) - Liu, Q.; Chen, X.-Y.; Puttreddy, R.; Rissanen, K.; Enders, D. (Angew. Chem., Int. Ed., 2018)

(untitled) - Liu, Q.; Wang, Z.-X.; Chen, X.-Y. (Org. Chem. Front., 2020)

(untitled) - Yao, Y.; Xu, L. (Mini-Rev. Org. Chem., 2016)

(untitled) - Chang, G.-H.; Wang, C.-Y.; Madhusudhan Reddy, G.; Tsai, Y.-L.; Lin, W. (J. Org. Chem., 2016)

(untitled) - Lin, H.; Tan, Y.; Wu, J.-M.; Yang, X.-D.; Chen, J.-H.; Sun, X.-W. (Tetrahedron Lett., 2015)

(untitled) - Nakamura, S.; Toda, A.; Sano, M.; Hatanaka, T.; Funahashi, Y. (Adv. Synth. Catal., 2016)

(untitled) - Li, X.; Yan, J.; Qin, J.; Lin, S.; Chen, W.; Zhan, R.; Huang, H. (J. Org. Chem., 2019)

(untitled) - Yan, J.; Li, X.; Chen, Y.; Li, Y.; Chen, W.; Zhan, R.; Huang, H. (J. Org. Chem., 2020)

(untitled) - Yuan, W.-C.; Lei, C.-W.; Zhao, J.-Q.; Wang, Z.-H.; You, Y. (J. Org. Chem., 2021)

(untitled) - Hejmanowska, J.; Albrecht, A.; Pięta, J.; Albrecht, Ł. (Adv. Synth. Catal., 2015)

(untitled) - Albrecht, A.; Skrzyńska, A.; Pietrzak, A.; Bojanowski, J.; Albrecht, Ł. (Asian J. Org. Chem., 2016)

(untitled) - Xia, A.-B.; Zhang, X.-L.; Tang, C.-K.; Feng, K.-X.; Du, X.-H.; Xu, D.-Q. (Org. Biomol. Chem., 2017)

(untitled) - Modrocká, V.; Veverková, E.; Mečiarová, M.; Šebesta, R. (J. Org. Chem., 2018)

(untitled) - Modrocká, V.; Veverková, E.; Baran, R.; Šebesta, R. (ChemistrySelect, 2018)

(untitled) - Zheng, J.; He, M.; Xie, B.; Yang, L.; Hu, Z.; Zhou, H.-B.; Dong, C. (Org. Biomol. Chem., 2018)

(untitled) - Gurubrahamam, R.; Gao, B.-F.; Chen, Y. m.; Chan, Y.-T.; Tsai, M.-K.; Chen, K. (Org. Lett., 2016)

(untitled) - Mei, R.-Q.; Xu, X.-Y.; Li, Y.-C.; Fu, J.-Y.; Huang, Q.-C.; Wang, L.-X. (Tetrahedron Lett., 2011)

(untitled) - Zhang, G.; Zhang, Y.; Yan, J.; Chen, R.; Wang, S.; Ma, Y.; Wang, R. (J. Org. Chem., 2012)

(untitled) - Chen, Y.-R.; Ganapuram, M. R.; Hsieh, K.-H.; Chen, K.-H.; Karanam, P.; Vagh, S. S.; Liou, Y.-C.; Lin, W. (Chem. Commun., 2018)

(untitled) - Suh, C. W.; Han, T. H.; Kim, D. Y. (Bull. Korean Chem. Soc., 2013)

(untitled) - Xiao, X.; Shao, B.-X.; Lu, Y.-J.; Cao, Q.-Q.; Xia, C.-N.; Chen, F.-E. (Adv. Synth. Catal., 2021)

(untitled) - Zhang, X.-Q.; Lv, X.-J.; Pei, J.-P.; Tan, R.; Liu, Y.-K. (Org. Chem. Front., 2020)

(untitled) - Maruoka, K. (Proc. Jpn. Acad., Ser. B, 2019)

(untitled) - Jew, S.-s.; Park, H.-g. (Chem. Commun., 2009)

(untitled) - Wang, H. (Catalysts, 2019)

(untitled) - Wang, J.; Zhang, S.; Ding, W.; Wang, C.; Chen, J.; Cao, W.; Wu, X. (ChemCatChem, 2020)

(untitled) - Bartlett, C. J.; Day, D. P.; Chan, Y.; Allin, S. M.; McKenzie, M. J.; Slawin, A. M. Z.; Bulman Page, P. C. (J. Org. Chem., 2012)